Effect of Pupal Exposure of Raisin Moth ,Ephestia figulilella (Gregson),(Lepidoptera:pyralidae) to High Temperature on Certain Biological Parameters of the Adult - M.A. Shawkit; A.A Al Taweel; L.J. AL-Bahadyli; N.S. Deab; N.A. M. khedher (مجلة بغداد للعلوم, 2007)
The pupal stage of Ephestia figulilella was exposed to temperature of 40 ,45 and 50 ºC for different period (1,3 and 6 hrs) besides the control  which exposed to 28 ºC .The effects of these temperature degrees were determined on some biological aspects of produced adult . Results showed that there is increasing in the percentage of dry dead pupa and malformed adults as the temperature and duration of exposure to it increased . Furthermore ,the mean number of eggs / female and  the  age percent of egg hatch for the following mating : ( exposed female × normal male , normal female × exposed male and exposed female × exposed male ) were also effected when adults exposed to these temperature as pupae .